Pengaruh Kompetensi Pedagogik Guru dan Lingkungan Belajar terhadap Motivasi Belajar Peserta Didik di SMPN 5 Lembang Jaya Kabupaten Solok - Ridhatul Husna; Gusril Kanedi; Juliana Batubara (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Increasing student learning achievement is influenced by the quality of the learning process in the classroom. Therefore, the learning process will run well if it is supported by teachers who have high competence. This research aims to reveal: 1. Description of teachers' pedagogical competence, 2. Description of the learning environment, 3. Description of students' learning motivation, 4. Significant influence of teachers' pedagogical competence on students' learning motivation, 5. Significant influence of the learning environment on participants' learning motivation students and 6. The significant influence of teacher pedagogical competence and the learning environment on students' learning motivation at SMPN 5 Lembang Jaya. This research uses ex post facto quantitative research methods. The population of this study was 95 people, using random sampling techniques referring to the Slovin formula, a sample of 77 people was obtained. Data collection instruments used a questionnaire with a Likert scale. The research results revealed that: (1) The description of teachers' pedagogical competence was categorized as good at 81.87%, (2) The description of the learning environment was categorized as good at 69.64%, (3). The description of students' learning motivation is categorized as high at 72.74%, (4) there is a significant influence between teacher pedagogical competence on students' learning motivation at 56%, (5) there is an insignificant influence of the learning environment on students' learning motivation at 29 %, and (6) there is a significant influence between teacher pedagogical competence and the learning environment on the learning motivation of students at SMPN 5 Lembang Jaya together at 57%.